Justice, Luck & Responsibility in Health Care
VIII, 232 p.
Keywords: In this book, an international group of philosophers, economists and theologians focus on the relationship between justice, luck and responsibility in health care. Together, they offer a thorough reflection on questions such as: How should we understand justice in health care? Why are health care interests so important that they deserve special protection? How should we value health? What are its functions and do these make it different from other goods? Furthermore, how much equality should there be? Which inequalities in health and health care are unfair and which are simply unfortunate? Which matters of health care belong to the domain of justice, and which to the domain of charity? And to what extent should we allow personal responsibility to play a role in allocating health care services and resources, or in distributing the costs? With this book, the editors meet a double objective. First, they provide a comprehensive philosophical framework for understanding the concepts of justice, luck and responsibility in contemporary health care; and secondly, they explore whether these concepts have practical force to guide normative discussions in specific contexts of health care such as prevention of infectious diseases or in matters of reproductive technology. Particular and extensive attention is paid to issues regarding end-of-life care.